DIGITAL TRANSFORMATION OF AGRICULTURE IN THE REPUBLIC OF KAZAKHSTAN - Kokenova A.T.; Sabenova B.N.; Mashirova T.N.; Aitymbetovа A.N.; Abylkasym A.B. (Academic Journal of Physical and Chemical Sciences, 2020)
Currently, in many countries, digitalization is a strategic development priority. According to the forecasts of the world's leading experts, by 2020 25% of the world economy will be digital, and the introduction of digitalization technologies for the economy, allowing the state, business and society to interact effectively, is becoming an increasingly large-scale and dynamic process. Agriculture in the world is turning from a traditional into a high-tech industry, which is able to create new markets for innovative developments that did not exist before. The time has come when intelligent digital solutions should help the country's agriculture to cope with the problems of increasing productivity and sustainable development. The agricultural sector is the most vulnerable sector of the economy, largely dependent on the vagaries of nature. And the impact of climate change on food security in the world will only increase. Intensity, seasonality and rainfall will become increasingly unpredictable, which will significantly reduce the ability of the agrarian business to adapt to such changes. Digitization of the agro-industrial complex will reduce these risks, adapt to climate change, increase crop yields and animal productivity, and plan field work in a timely manner. The agricultural sector of Kazakhstan is of great importance and should continue to develop rapidly. However, due to the natural conditions in the country, that is, due to the harsh continental climate, this is not easy, but because of the large territory, this industry has great potential. Kazakhstan could make an important contribution to the global food supply in the future. Reducing the cost of growing products, improving their quality and competitiveness based on the efficient use of resources and scientifically based approaches is the main task of digitization of agriculture. Providing the necessary information to rural producers will reduce transaction costs for the purchase and sale, simplify the supply chain of products from the field to the consumer, reduce the deficit in skilled labor.